STRATEGIC SIGNALING AND NEW TECHNOLOGICALLY SUPERIOR PRODUCT INTRODUCTION: A GAME-THEORETIC MODEL WITH SIMULATION - Tavana, Madjid; Caprio, Debora Di; Santos-Arteaga, Francisco J. (Technological and Economic Development of Economy)

A novel two-stage DEA production model with freely distributed initial inputs and shared intermediate outputs - Izadikhah, Mohammad; Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Expert Systems with Applications)

A novel genetic algorithm based method for solving continuous nonlinear optimization problems through subdividing and labeling - Esmaelian, Majid; Tavana, Madjid; Santos-Arteaga, Francisco J.; Vali, Masoumeh (Measurement)

A new dynamic range directional measure for two-stage data envelopment analysis models with negative data - Tavana, Madjid; Izadikhah, Mohammad; Di Caprio, Debora; Farzipoor Saen, Reza (Computers & Industrial Engineering)

An aggregation method for solving group multi-criteria decision-making problems with single-valued neutrosophic sets - Sodenkamp, Mariya A.; Tavana, Madjid; Di Caprio, Debora (Applied Soft Computing)

An Artificial Neural Network and Bayesian Network model for liquidity risk assessment in banking - Tavana, Madjid; Abtahi, Amir-Reza; Di Caprio, Debora; Poortarigh, Maryam (Neurocomputing)

An integrated location-inventory-routing humanitarian supply chain network with pre- and post-disaster management considerations - Tavana, Madjid; Abtahi, Amir-Reza; Di Caprio, Debora; Hashemi, Reza; Yousefi-Zenouz, Reza (Socio-Economic Planning Sciences)

A hybrid DEA-MOLP model for public school assessment and closure decision in the City of Philadelphia - Tavana, Madjid; Ebrahimnejad, Ali; Santos-Arteaga, Francisco J.; Mansourzadeh, Seyed Mehdi; Matin, Reza Kazemi (Socio-Economic Planning Sciences)

Efficiency decomposition and measurement in two-stage fuzzy DEA models using a bargaining game approach - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos Arteaga, Francisco J.; Mahmoudi, Reza; Hafezalkotob, Ashkan (Computers & Industrial Engineering)

A discrete cuckoo optimization algorithm for consolidation in cloud computing - Tavana, Madjid; Shahdi-Pashaki, Saleh; Teymourian, Ehsan; Santos-Arteaga, Francisco J.; Komaki, Mohammad (Computers & Industrial Engineering)

The value of information as a verification and regret-preventing mechanism in algorithmic search environments - Tavana, Madjid; Santos-Arteaga, Francisco J.; Di Caprio, Debora (Information Sciences)

An extended stochastic VIKOR model with decision maker's attitude towards risk - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Algorithms for Max-Min Share Fair Allocation of Indivisible Chores - Aziz, Haris; Rauchecker, Gerhard; Schryen, Guido; Walsh, Toby (Thirty-First AAAI Conference on Artificial Intelligence (AAAI-17))
We consider Max-min Share (MmS) fair allocations of indivisible chores (items with negative utilities). We show that allocation of chores and classical allocation of goods (items with positive utilities) have some fundamental connections but also differences which prevent a straightforward application of algorithms for goods in the chores setting and viceversa. We prove that an MmS allocation does not need to exist for chores and computing an MmS allocation - if it exists - is strongly NP-hard. In view of these non-existence and complexity results, we present a polynomial-time 2-approximation algorithm for MmS fairness for chores. We then introduce a new fairness concept called optimal MmS that represents the best possible allocation in terms of MmS that is guaranteed to exist. We use connections to parallel machine scheduling to give (1) a polynomial-time approximation scheme for computing an optimal MmS allocation when the number of agents is fixed and (2) an effective and efficient heuristic with an ex-post worst-case analysis.

Exploring the Scientific Impact of Information Systems Design Science Research: A Scientometric Study - Wagner, Gerit; Prester, Julian; Schryen, Guido (38th International Conference on Information Systems)
Design science is a fundamental research stream that contends its position in the information systems discipline. While ongoing debates address the relative importance of design science contributions in the information systems community, insights into the scientific impact of design science research (DSR) are missing and this lack of understanding arguably poses challenges to an informed discourse. To identify the most influential papers and those factors that explain their scientific impact, this paper presents an exploratory study of the scientific impact of DSR papers published in the AIS Senior Scholars' Basket of Journals. We uncover the current DSR landscape by taking stock of influential papers and theories and develop a model to explain the scientific impact of DSR papers. Our findings show that scientific impact is significantly explained by theorization and novelty. We discuss how the implications of our work can be projected on the overarching discourse on DSR.

High-Performance Business Computing - Effizienzsteigerung durch Parallelisierung - Schryen, Guido; Hristova, Diana (Smart Data Radar (Deutsche Bank))

Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields? - Schryen, Guido; Benlian, Alexander; Rowe, Frantz; Shirley, Gregor; Larsen, Kai; Petter, Stacie; Paré, Guy; Wagner, Gerit; Haag, Steffi; Yasasin, Emrah (Communications of the AIS)
Literature reviews (LRs) are recognized for their increasing impact in the information systems literature. Methodologists have drawn attention to the question of how we can leverage the value of LRs to preserve and generate knowledge. The panelists who participated in the discussion of ?Standalone Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields?? at ICIS 2016 in Dublin acknowledged this significant issue and debated a) what the IS field can learn from other fields and where IS-specific challenges occur, b) how the IS field should move forward to foster the genre of LRs, and c) what best practices are to train doctoral IS students in publishing LRs. This article reports the key takeaways of this panel discussion. Guidance for IS scholars is provided on how to conduct LRs that contribute to the cumulative knowledge development within and across the IS field to best prepare the next generation of IS scholars.
Keywords: Literature Review; Review Methodology; Research Methodology; Doctoral Training

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

Simulating Storage Policies for an Automated Grid-Based Warehouse System - Beckschäfer, Michaela; Malberg, Simon; Tierney, Kevin; Weskamp, Christoph (Lecture Notes in Computer Science)

An application of an integrated ANP–QFD framework for sustainable supplier selection - Tavana, Madjid; Yazdani, Morteza; Di Caprio, Debora (International Journal of Logistics Research and Applications)

Drone shipping versus truck delivery in a cross-docking system with multiple fleets and products - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos-Arteaga, Francisco J.; Zandi, Mohammad-Hossein (Expert Systems with Applications)

The effect of preference similarity on the formation of clusters and the connectivity of social networks - Tavana, Madjid; Santos-Arteaga, Francisco J.; Di Caprio, Debora (Computers in Human Behavior)

A fuzzy multi-criteria spatial decision support system for solar farm location planning - Tavana, Madjid; Santos Arteaga, Francisco J.; Mohammadi, Somayeh; Alimohammadi, Moslem (Energy Strategy Reviews)

A multi-objective multi-state series-parallel redundancy allocation model using tuned meta-heuristic algorithms - Alikar, Najmeh; Mousavi, Seyed Mohsen; Tavana, Madjid; Niaki, S.T.A. (International Journal of Systems Science: Operations & Logistics)

The emergence of inclusive and exclusive virtual communities determined by the preferences of their users - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Journal of Ambient Intelligence and Humanized Computing)

A hybrid goal programming and dynamic data envelopment analysis framework for sustainable supplier evaluation - Tavana, Madjid; Shabanpour, Hadi; Yousefi, Saeed; Farzipoor Saen, Reza (Neural Computing and Applications)

Fuzzy chance-constrained geometric programming: the possibility, necessity and credibility approaches - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi; Di Caprio, Debora (Operational Research)

A novel method for selecting a single efficient unit in data envelopment analysis without explicit inputs/outputs - Toloo, Mehdi; Tavana, Madjid (Annals of Operations Research)

Innovation dynamics and labor force restructuring with asymmetrically developed national innovation systems - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; O’Connor, Aidan (International Business Review)

A multiple correspondence analysis model for evaluating technology foresight methods - Esmaelian, Majid; Tavana, Madjid; Di Caprio, Debora; Ansari, Reza (Technological Forecasting and Social Change)

A customized genetic algorithm for solving multi-period cross-dock truck scheduling problems - Khalili-Damghani, Kaveh; Tavana, Madjid; Santos-Arteaga, Francisco J.; Ghanbarzad-Dashti, Mahdokht (Measurement)

A flexible cross-efficiency fuzzy data envelopment analysis model for sustainable sourcing - Hatami-Marbini, Adel; Agrell, Per J.; Tavana, Madjid; Khoshnevis, Pegah (Journal of Cleaner Production)

FORMALISING THE DEMAND FOR TECHNOLOGICAL INNOVATIONS: RATIONAL HERDS, MARKET FRICTIONS AND NETWORK EFFECTS - SANTOS-ARTEAGA, FRANCISCO J.; CAPRIO, DEBORA DI; Tavana, Madjid; O'CONNOR, AIDAN (International Journal of Innovation Management)

A Novel Decision Support Framework for Computing Expected Utilities from Linguistic Evaluations - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

A bi-objective multi-period series-parallel inventory-redundancy allocation problem with time value of money and inflation considerations - Alikar, Najmeh; Mousavi, Seyed Mohsen; Ghazilla, Raja Ariffin Raja; Tavana, Madjid; Olugu, Ezutah Udoncy (Computers & Industrial Engineering)

Application of the NSGA-II algorithm to a multi-period inventory-redundancy allocation problem in a series-parallel system - Alikar, Najmeh; Mousavi, Seyed Mohsen; Raja Ghazilla, Raja Ariffin; Tavana, Madjid; Olugu, Ezutah Udoncy (Reliability Engineering & System Safety)

A redundancy detection algorithm for fuzzy stochastic multi-objective linear fractional programming problems - Khanjani Shiraz, Rashed; Charles, Vincent; Tavana, Madjid; Di Caprio, Debora (Stochastic Analysis and Applications)

A multi-user decision support system for online city bus tour planning - Bagloee, Saeed Asadi; Tavana, Madjid; Di Caprio, Debora; Asadi, Mohsen; Heshmati, Mitra (Journal of Modern Transportation)

A logit-based model for measuring the effects of transportation infrastructure on land value - Asadi Bagloee, Saeed; Heshmati, Mitra; Tavana, Madjid; Di Caprio, Debora (Transportation Planning and Technology)

Recent Fuzzy Generalisations of Rough Sets Theory: A Systematic Review and Methodological Critique of the Literature - Mardani, Abbas; Nilashi, Mehrbakhsh; Antucheviciene, Jurgita; Tavana, Madjid; Bausys, Romualdas; Ibrahim, Othman (Complexity)

A multi-criteria perception-based strict-ordering algorithm for identifying the most-preferred choice among equally-evaluated alternatives - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Projekt KUBAS: Koordination ungebundener Vor-Ort-Helfer - Rauchecker, Gerhard; Schryen, Guido (Im Einsatz)

Factors Affecting the Scientific Impact of Literature Reviews: A Scientometric Study - Wagner, Gerit; Prester, Julian; Roche, Maria; Benlian, Alexander; Schryen, Guido (International Conference on Information Systems)

Development of two novel face-recognition CAPTCHAs: a security and usability study - Schryen, Guido; Wagner, Gerit; Schlegel, Alexander (Computers & Security)
CAPTCHAs are challenge-response tests that aim at preventing unwanted machines, including bots, from accessing web services while providing easy access for humans. Recent advances in artificial-intelligence based attacks show that the level of security provided by many state-of-the-art text-based CAPTCHAs is declining. At the same time, techniques for distorting and obscuring the text, which are used to maintain the level of security, make text-based CAPTCHAs diffcult to solve for humans, and thereby further degrade usability. The need for developing alternative types of CAPTCHAs which improve both, the current security and usability levels, has been emphasized by several researchers. With this study, we contribute to research through (1) the development of two new face recognition CAPTCHAs (Farett-Gender and Farett-Gender&Age), (2) the security analysis of both procedures, and (3) the provision of empirical evidence that one of the suggested CAPTCHAs (Farett-Gender) is similar to Google's reCAPTCHA and better than KCAPTCHA concerning effectiveness (error rates), superior to both regarding learnability and satisfaction but not effciency.
Keywords: CAPTCHA; Usability; Facial features; Gender classiffcation; Age classification; Face recognition reverse Turing test

A secured context-aware tourism recommender system using artificial bee colony and simulated annealing - Roy, Arup; Tavana, Madjid; Banerjee, Soumya; Caprio, Debora Di (International Journal of Applied Management Science)

Robust efficiency measurement with common set of weights under varying degrees of conservatism and data uncertainty - Aghayi, Nazila; Tavana, Madjid; Raayatpanah, Mohammad Ali (European J. of Industrial Engineering)

Optimistic and pessimistic performance and congestion analysis in fuzzy data envelopment analysis - Khodabakhshi, Mohamad; Tavana, Madjid; Abootaleb, Fatemeh Baghbani (International Journal of Logistics Systems and Management)

Autonomous vehicles: challenges, opportunities, and future implications for transportation policies - Bagloee, Saeed Asadi; Tavana, Madjid; Asadi, Mohsen; Oliver, Tracey (Journal of Modern Transportation)

A bi-objective inventory optimization model under inflation and discount using tuned Pareto-based algorithms: NSGA-II, NRGA, and MOPSO - Mousavi, Seyed Mohsen; Sadeghi, Javad; Niaki, Seyed Taghi Akhavan; Tavana, Madjid (Applied Soft Computing)

An Improved Method for Edge Detection and Image Segmentation Using Fuzzy Cellular Automata - Shahverdi, Reza; Tavana, Madjid; Ebrahimnejad, Ali; Zahedi, Khadijeh; Omranpour, Hesam (Cybernetics and Systems)

An integrated data envelopment analysis and free disposal hull framework for cost-efficiency measurement using rough sets - Khanjani Shiraz, Rashed; Fukuyama, Hirofumi; Tavana, Madjid; Di Caprio, Debora (Applied Soft Computing)